A6.36 Characterisation of anti-JO1 autoantibodies in myositis. (13th February 2015) - Fernandes-Cerqueira, C; Lundberg, I; Jakobsson, PJ
Abstract : Background and objectives: Anti-histidyl tRNA synthetase (Jo1) autoantibodies are the most common type of myositis specific autoantibodies, being present in 15%–30% of the patients. When myositis patients develop simultaneous interstitial lung disease the percentage of patients positive for anti-Jo1 autoantibodies can reach approximately 70%. These individuals are generally characterised by a condition called anti-synthetase syndrome known to present a particular clinical phenotype affecting the muscles, lungs, joints and skin. Little is known about the functional role of anti-Jo1 autoantibodies. The aim of this study was to purify anti-Jo1 IgG from blood of myositis patients, determine the proportion in circulation and further characterise any molecular effects of these autoantibodies. Materials and methods: Sera (n = 42) samples from anti-Jo1 positive myositis patients were collected and used to affinity purify anti-Jo1 IgG. Recombinant human Jo1 (rJo1) was over-expressed in E.coli competent cells, purified from the cytosolic fraction using hydroxyapatite followed by strong anion exchange chromatography and coupled to an NHS activated pre-packed sepharose column. Anti-Jo1 IgGs were isolated from total IgGs extracted from pooled myositis sera using a ProteinG column and further purified using the Jo1 column. The abundance of anti-Jo1 IgG in serum from myositis patients was estimated by measuring the absorbance at 280 and 595 nm. Recovery/purity and reactivity against rJo1 was analysed by SDS-PAGE and western blot, respectively. Results: Anti-Jo1 IgGs were successfully purified from myositis serum using an in-house developed Jo1 affinity column. Among the total percentage of IgG 1.5% were Jo1 reactive (anti-Jo1 IgG). The total concentration of anti-Jo1 IgG in myositis serum was estimated to be 180 μg/ml. Anti-Jo1 IgG recognised both the monomer and the dimer structure of the enzyme. Conclusions: Anti-Jo1 IgGs were efficiently purified from myositis serum and the proportion and concentration was estimated. Affinity purified anti-Jo1 autoantibodies are currently being used as molecular tools in in vivo and in vitro experiments for the characterisation of functional effects and antigen/autoantibody dynamics in myositis.